Nikah Mut'ah From The Perspective Of The Hadith Of The Prophet Pbuh - Nur Rahman; Zulkifli; Jumni Nelli (al-Battar: Jurnal Pamungkas Hukum, 2024)
The Hadith on the law of mut'ah marriage has been around for a long time, and it has raised two mainstream opinions that prohibit and enable it, the first being referred to as the Sunnah clerical reference, while the second one is referring to the opinion of Shi'ite scholars. Sunnah scholars argue that mutahah marriage does not instill permanent family life, facilitates freesex life and is free of marital responsibilities. While the Shi'ite scholars say that the marriage was approved by the Prophet Muhammad. and its ability to last forever. Mutual marriage is an interesting and unique phenomenon to study. Therefore, this study is a perspective study of hadith, so the approach used is the hadith approach to discover the clarity of the status of the hadith. Based on the method used, it is revealed that the hadith contained sanad and matan shahih. Mut'ah marriage is generally forbidden until the Day of Judgment. This is based on the matn of the hadith which states temporally that mut'ah marriage has been permitted, however, then it is prohibited forever. Mut'ah marriage in terms of benefits, then there is no sakinah, mawaddah, wa rahmah in it. The government must more firmly forbid mut'ah marriage. Because, mut'ah marriage is still done by the community. The government must provide legal protection for mut'ah marriage victims. Because this marriage has legal effects on children born from the marriage.